Literature Review on Current Trends in Healthcare Systems (International Journal of Progressive Research and Innovation in Science, Engineering, Technology, Commerce, Management and Law (IJPRISETCML), 2025)
The integration of technology in patient care is essential for improving healthcare outcomes and enhancing the overall patient experience. The adoption of advanced technologies can facilitate personalized treatment plans, thereby significantly improving patient engagement and satisfaction. Personalized treatment plans not only enhance patient adherence but also empower them with a deeper understanding of their conditions and options for care (Ugemuge et al., n.d.).
Keywords: Technology Integration in Healthcare; Patient-Centered Care; Digital Health Innovations; Artificial Intelligence in Healthcare; Telemedicine and mHealth